5-3x=-6x-12

Simple and best practice solution for 5-3x=-6x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3x=-6x-12 equation:


Simplifying
5 + -3x = -6x + -12

Reorder the terms:
5 + -3x = -12 + -6x

Solving
5 + -3x = -12 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
5 + -3x + 6x = -12 + -6x + 6x

Combine like terms: -3x + 6x = 3x
5 + 3x = -12 + -6x + 6x

Combine like terms: -6x + 6x = 0
5 + 3x = -12 + 0
5 + 3x = -12

Add '-5' to each side of the equation.
5 + -5 + 3x = -12 + -5

Combine like terms: 5 + -5 = 0
0 + 3x = -12 + -5
3x = -12 + -5

Combine like terms: -12 + -5 = -17
3x = -17

Divide each side by '3'.
x = -5.666666667

Simplifying
x = -5.666666667

See similar equations:

| 2x^3-15x^2+36x+1=0 | | 3x-1=5y-9 | | abs(z)+z^2=0 | | x^2dy-y^2dx=0e | | lgx+[5(x+1)]=2 | | 5y-3x=72+5x | | 31+3a=4(7a+5) | | 34*380= | | 1/6(5x-4) | | 2(a+0.3)=1.2(a-4) | | 2x*4y+7(1x-2y)= | | 2x*4+7(1x-2y)= | | (4+x)*x=3 | | (4+1)*x=3 | | (3+5)*x=43 | | (3+5)*x=x | | X/2700=X-6570 | | 3x+7=-1+2x | | z^2-(3-4i)z-1-5i=0 | | X=X-65 | | P(x)=-x^3-x^2+x | | z^2=6+2i | | ,/,jhgtffrfg | | (x-5)=(3x-20) | | cos(x)=7x | | x+87948955270000000000=87948955270000000000 | | 2x+1+1+1+1+1+1+1+1+1+1+1+1+1+1+-5+1+1+1+1+1+1+1+1*5-5+0+4147589462014587102-45555555555555555+55555555555555-200000000000000000000+20000000000000000000=0 | | x-(.3x)=1200 | | 20(2n-1)=11(n-1)(n-2) | | d(p)=35ln(150-5p) | | 2sinx=2+2cosx | | 3x^2-17x-2=0 |

Equations solver categories